Program Pembelajaran Hubungan Masyarakat Dan Peranan Pentingnya Dalam Meningkatkan Pemberdayaan Sumber Daya Manusia Di Dharma Wanita Persatuan Dinas Pertanian Dan Ketahanan Pangan Kabupaten Banyumas - Poppy Fitrijanti Soeparan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Communication plays a very important role in human life. Because wherever there are humans, that’s where communication occurs. So, it is important to have and increase knowledge about communication. Not only communication between individuals in daily life, but also between individuals in organization. It is very crucial to create good and targeted communication between individuals within it, to create harmony and to avoid misunderstanding. All people and organizations live in relation to their environment. To improve the quality of this relationship, good communication is needed. Improving the quality of this communication is the field of activity of public relations. Every organization from initial to final activities will go through various integrated activities so as to achieve the best results. The glue of all these activities is the field of Public Relations activities. In the society, also in organizations, we need to know about Public Relations. Because in organization, what is very important to pay attention to is how individuals in the organizations create and develop good ways of communicating with each other. So that all organizational works can be carried out well and produce the best results. Apart from being a good goal for the organization itself, knowledge of Public Relations can also be useful for individual Dharma Wanita members to continue to improve their own quality and empower themselves even more, so that they can continue to carry out activities with other individuals in public. This increase in capability correlates with an increase in the quality of human resources, in this case Dharma Wanita members.